Effect of oral administration of mushroom Panaeolus infusion on motoric activity and curiousity of male mice - Andreanus A. Soemardji; IG.N.A. Supradja (Indonesian Journal of Pharmacy, 2003)
The motoric activity and the curiosity tests on Swiss Webster male mice orally treated with infusion of mushroom panaeolus were studied. A 10% infusion of mushroom administered orally at the dose of 0.5; 1.0 and 2.0 g/kg of body weight showed to decrease in motoric activity and curiousity, but the decrease was less than that shown by diazepam with the dose 5 mg/kg body weight administered intraperitoneally.Keywords :Mushroom, Panaeolus, motoric activity, curiousity.